1989
DOI: 10.1113/expphysiol.1989.sp003374
|View full text |Cite
|
Sign up to set email alerts
|

Receptor‐controlled Calcium Discharge in Frog Heart Cells

Abstract: SUMMARYA brief account is given of previous work concerned with the effects which ATP (P2-'purinergic') and a-adrenaline receptors have on the activity of the sarcoplasmic reticulum (SR) in frog heart atrial cells. More recent experiments made with single atrial trabeculae are also described which suggest, among other things, that ATP and a-adrenaline receptors both facilitate the process by which an action potential induces SR calcium discharge in atrial heart cells. The facilitatory effect involved is consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The effects of isoprenaline, as well as of variation in [Ca2+]o and stimulation pattern, on all the twitch characteristics, as reported in the present paper, are comparable to those described by previous investigators for multicellular atrial and ventricular preparations from frog heart under similar experimental conditions (Blinks & Koch-Weser, 1963;Chapman & Niedergerke, 1970;Allen & Blinks, 1978;Tung & Morad, 1983;Niedergerke & Page, 1989). In accordance with Tung & Morad (1988), therefore, it can be concluded that the enzymatic isolation procedure does not alter the physiological properties of the myocytes which represent a reliable preparation for the study of myocardial-contraction mechanics.…”
Section: Integrity Of Enzymatically Isolated Myocytessupporting
confidence: 91%
“…The effects of isoprenaline, as well as of variation in [Ca2+]o and stimulation pattern, on all the twitch characteristics, as reported in the present paper, are comparable to those described by previous investigators for multicellular atrial and ventricular preparations from frog heart under similar experimental conditions (Blinks & Koch-Weser, 1963;Chapman & Niedergerke, 1970;Allen & Blinks, 1978;Tung & Morad, 1983;Niedergerke & Page, 1989). In accordance with Tung & Morad (1988), therefore, it can be concluded that the enzymatic isolation procedure does not alter the physiological properties of the myocytes which represent a reliable preparation for the study of myocardial-contraction mechanics.…”
Section: Integrity Of Enzymatically Isolated Myocytessupporting
confidence: 91%
“…In frog heart cells ATP or alpha adrenaline action causes additional calcium discharge from the sarcoplasmic reticulam (SR) in association with the action potential (Niedergerke and Page, 1989). In contrast, acetylcholine with G Protein coupled muscarinic (M 2 ) receptor on surface of frog heart muscle cells produces negative inotropic and negative chronotropic effects (Gattuso et al, 1999;Kulkarn, 1999).…”
Section: Samplementioning
confidence: 97%
“…Acetaldehyde shortened APD 90 although APD 30 was lengthened. In contrast to acetaldehyde, adrenaline or isoprenaline, which was demonstrated to enhance I Ca , prolonged APD 90 in frog atrial myocytes [18,19]. This suggests different mechanisms of acetaldehyde from those of β-adrenergic agents.…”
Section: Discussionmentioning
confidence: 72%